Inoculated Soybean Yields Response to Nitrogen and Phosphorus Application - Phiri, Austin T.; Muindi, Esther M.; Omollo, Jacob Omondi; Yegon, Rebecca; Kausiwa, Daniel (SCIENCEDOMAIN international, 2016)
Inherent low soil nitrogen (N) and phosphorus (P) is one of the major hindrances of increased soybean productivity in Malawian soils. Although, inoculation of legumes with rhizobia, has been advocated for decades as a way of boosting leguminous crops’ productivity through biological nitrogen fixation (BNF), the effectiveness of this strategy, has been low. An experiment was carried out to investigate the effect of the application of small doses of N and P to inoculated soybean. It was laid out in a complete block design (CBD) replicated three times and the treatments included: 1. Soybean only, 2. Inoculated soybean, 3. Inoculated soybean + 30 kg N ha-1, 4. Inoculated soybean + 30 kg N ha-1 + 25 kg P ha-1, 5. Inoculated soybean + 30 kg N ha-1 + 35 kg P ha-1. The soybean in all treatment plots except for treatment 1 was inoculated with 30 kg N ha-1 applied as urea to treatment plots 3, 4 and 5. Phosphorus as TSP was applied to treatment 4 and 5 at the rate of 25 and 35 kg P ha-1. Data collected included; selected soil physical and chemical properties,biomass and pod yields. Data obtained were subjected to Analysis of Variance (ANOVA) using the GenStat statistical package and treatment effects tested for significance using the F-test at 5% level of significance. Means were separated using the least significant difference (P<0.05). Results indicate that inoculating soybean with rhizobia and inoculating soybean with rhizobia plus applying 30 kg N ha-1 did not significantly increase biomass yields. However, inoculating soybean plus the combined application of 30 kg N ha-1 and, 25 kg P ha-1 or / and 35 kg P ha-1 increased the soybean biomass yields by 54% and 70% respectively above control. The lack of significant response when N was applied without P points to the significant role played by phosphorus in root development and energy transfer processes within the plant. Effective nodulation, however, was significantly higher (p<0.05) above the control where inoculation was combined with the application of 30 kg N ha-1 and 35 kg P ha-1, hence underlining the role played by phosphorus in nodule development and the role of starter N in soils low in N.
DOI: 10.9734/IJPSS/2016/24905
Keywords: Soybean; inoculation; biomass; biological nitrogen fixation